Clinician perceptions of common mental disorders before and after implementation of a consultation-liaison psychiatry service: a longitudinal qualitative study in government-operated primary care settings in Penang, Malaysia. Issue 6 (30th June 2021) - Russell, Vincent; Loo, Ching Ee; Walsh, Aisling; Bharathy, Arokiamary; Vasudevan, Umadevi; Looi, Irene; Smith, Susan M
Abstract : Objectives: To explore primary care clinician perceptions of barriers and facilitators in delivering care for common mental disorders (CMD) before and after implementation of a consultation-liaison psychiatry service (Psychiatry in Primary Care (PIPC)) in government-operated primary care clinics and to explore the clinicians' experience of the PIPC service itself. Design: This longitudinal qualitative study was informed by the Normalisation Process Model and involved audiotaped semi-structured individual interviews with front-line clinicians before (Time 1) and after (Time 2) the PIPC intervention. The Framework Method was used in the thematic analysis of pre/post interview transcripts. Setting: Two government-operated primary care clinics in Penang, Malaysia. Participants: 17 primary care medical, nursing and allied health staff recruited purposely to achieve a range of disciplines and a balanced representation from both clinics. Intervention: Psychiatrists, accompanied by medical students in small numbers, provided one half-day consultation visit per week, to front-line clinicians in each clinic over an 8-month period. The service involved psychiatric assessment of patients with suspected CMDs, with face-to-face discussion with the referring clinician before and after the patient assessment. Results: At Time 1 interviewees tended to equate CMDs with stress and embraced a holistic model of care while also reporting considerable autonomy in mental healthcare and positively appraising their current practices. At Time 2, post-intervention, participants demonstrated a shift towards greater understanding of CMDs as treatable conditions. They reported time pressures and the demands of key performance indicators in other areas as barriers to participation in PIPC. Yet they showed increased awareness of current service deficits and of their potential in delivering improved mental healthcare. Conclusions: Despite resource-related and structural barriers to implementation of national mental health policy in Malaysian primary care settings, our findings suggest that front-line clinicians are receptive to future interventions designed to improve the mental healthcare capacity.